MINI REVIEW: PEMANFAATAN GLUKOMANAN UMBI PORANG SEBAGAI EDIBLE PACKAGING DENGAN PENAMBAHAN EKSTRAK TANAMAN SEBAGAI BIOINDIKATOR MASA SIMPAN BAHAN PANGAN - Arif Nur Sho’im; Subur P. Pasaribu; Aman Sentosa Panggabean (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Edible packaging based on biopolymers offers an innovative solution to the problem of conventional plastic packaging waste that is difficult to degrade. Glucomannan from porang tuber (Amorphophallus muelleri Blume) is a natural biopolymer with great potential as a material for making edible packaging because it is biodegradable, safe, has good mechanical properties, and is sustainable. Glucomannan-based films can maintain the quality and extend the shelf life of food products. Further development is carried out through the integration of plant extracts containing anthocyanins as smart indicators to detect the freshness of food materials. Anthocyanins have high sensitivity to pH changes, allowing color changes in the packaging as the food quality degrades due to microbial activity. Thus, the combination of glucomannan and anthocyanins can produce smart edible packaging that is not only environmentally friendly but also capable of providing real-time visual information on the freshness of food products. Keywords: Edible packaging, glucomannan, konjac, anthocyanin, pH indicator.